Taking in account measuring errors of volume conversion devices in measuring of the volume of natural gas - Cimerman, Franc (Strojniški vestnik, 2016)
In order to measure standard volumes of natural gas we use volume-conversion devices (VCDs) or correctors. The European standard EN 12405-1 specifies the requirements and tests for the construction, performance, safety and conformity of VCDs associated with gas meters. VCDs are used to convert measurement flow, temperature, pressure and gas composition under operating conditions into base conditions. Gas-volume conversion devices consist of a calculator and a temperature transducer, or a calculator, a temperature transducer and a pressure transducer that are locally installed. On the basis of this standard we separate VCDs into type 1 and type 2. Type 1 VCDs are complete instruments, while type 2 VCDs are made of separate elements. The measuring errors for type 1 VCDs are determined for three different temperature ranges and for five different pressures. With the intention of determining the detected quantity of natural gas as accurately as possible, this article introduces the possibility of using measurement errors that are obtained by the national verification procedure. With the European MID (Measuring Instrument Directive 2004/22/EC) the maximum permissible error for type 1 and type 2 VCDs is "0.5". Using the suggested methods of implementing measurement errors in this article, we can meet the MID requirements for any type 1 and type 2 VCDs, the estimated measurement uncertainty, in addition to the 1/3 tolerable measuring errors, also takes into account the measurement uncertainty from the approximation of the proposed method. For different electronic natural-gas VCDs we wish to approximate the measurement errors that are determined during their testing using the regression method of least squares and determine the model%s characteristics. On the basis of a data analysis this article proposes statistical measures for determining the suitability of the regression model for a particular VCD. This article also proposes a verification procedure for taking into account experimental design theory, regression analysis, and a reduced number of measurement points. The proposed method is suitable for both types of VCDs.
Keywords: korektorji; merilna negotovost; merilni postopki; multiregresija; naprave za pretvarjanje prostornin